2021
DOI: 10.3390/w13223238
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Elements in Typical Mussels from the Southern Coast of Africa (Namibia, South Africa, Mozambique): Safety Aspect

Abstract: The soft tissues of mussels are often used as the main food source, especially in coastal areas. Neutron Activation Analysis was used to measure the content of 24 macro- and microelements in the soft tissues and 18 elements in the shells of selected sets of mussels of the species Mytilus galloprovincialis. The mussels were collected in 8 polluted and 4 pristine zones, which included Namibia, the west and east coasts of South Africa, and Mozambique. According to factor analysis Co, Ni, Zn, As, Se, Br, I, Sb cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…An Algerian study on the same species found a moderate human health risk from Fe and Cr and advised human consumers of wild mussels to eat no more than 500 g of mussel flesh per day [125]. To date, very little Southern African research has assessed the human health risk of consuming wild mussels via these indexes [16,113]. The two studies that were performed showed that recreational collectors should eat no more than 250 g of fresh mussels per week from South Africa (with even lower limits for Namibian and Mozambican mussels) to minimise their risk of negative health impacts from TEs [16,113].…”
Section: Trace Elementsmentioning
confidence: 99%
See 2 more Smart Citations
“…An Algerian study on the same species found a moderate human health risk from Fe and Cr and advised human consumers of wild mussels to eat no more than 500 g of mussel flesh per day [125]. To date, very little Southern African research has assessed the human health risk of consuming wild mussels via these indexes [16,113]. The two studies that were performed showed that recreational collectors should eat no more than 250 g of fresh mussels per week from South Africa (with even lower limits for Namibian and Mozambican mussels) to minimise their risk of negative health impacts from TEs [16,113].…”
Section: Trace Elementsmentioning
confidence: 99%
“…To date, very little Southern African research has assessed the human health risk of consuming wild mussels via these indexes [16,113]. The two studies that were performed showed that recreational collectors should eat no more than 250 g of fresh mussels per week from South Africa (with even lower limits for Namibian and Mozambican mussels) to minimise their risk of negative health impacts from TEs [16,113]. More local, published research is needed to properly assess the benefits and risks of wild mussel consumption along the South African coastline.…”
Section: Trace Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mussels, as sessile filter-feeders, have been used as sentinels, indicating environmental pollution [16][17][18], which has led to an extensive monitoring program by the US EPA that is known as the Mussel Watch program [19]. This has also inspired other national and international monitoring programs worldwide.…”
Section: Introductionmentioning
confidence: 99%